ESTIMASI TINGKAT BI RATE BERDASARKAN FAKTOR NILAI TUKAR (KURS USD/RP), JUB, INFLASI, IHSG DAN PDB MENGGUNAKAN METODE ADAPTIVE NEURO FUZZY INFERENCE SYSTEM (ANFIS) - Kahfi, Akhmad; Akhirson, Armaini (Prosiding PESAT, 2013)
This study aims to analyze and compare the sensitivity of macroeconomic variables onstock returns of agriculture, mining, manufacturing and finance in Indonesia StockExchange during the period 2008-2010. Independent variable used is the inflation rate,interest rates SBI and the exchange rate of U.S. dollar to rupiah . The dependentvariable used is stocks returns of agriculture, mining, manufacturing and finance. Theresearch method used is multiple linear regression analysis. From the results of researchcan be concluded that: (i) In partially, only SBI variables which affecting the agriculturalsector stock returns. In the mining sector, only SBI and EXCHANGE rate which affectingstock returns. In manufacturing and financial sector is only influenced by EXCHANGErate. (ii) In simultaneously macroeconomic variables could affect the stock returns of allsectors with the highest sensitivity levels in the mining, then agriculture and financialsectors, and the lowest sensitivity level of the manufacturing sector.